The application of Malay wood carving on contemporary architecture in Malaysia - Nila Inangda Manyam Keumala Daud; Ezrin Arbi; Mohammad Faisal (Journal of Design and the Built Environment, 2012)
Malay wood carving has been identified as one of the most important element in Malay Traditional Architecture. The application of this special element has its own philosophy and its purpose was meant to enrich the architecture character values. Issues are currently raised that the application of the Malay wood carving on contemporary architecture in Malaysia has ignored its unique original concept and philosophy. This indicate that the development of Malay Wood Carving requires attention and need more encouragement in order to catch up with the vast development of architecture in Malaysia, and overcome the problem of introducing more meaningful Malay wood carving in contemporary architecture building. A research has been conducted to investigate the thread of the development and application of Malay wood carving in contemporary architecture based on case study of a five star hotel in Kuala Lumpur.